Microleakage of hydrophilic adhesive systems in Class V composite restorations - Amaral, Cristiane M.; Hara, Anderson Takeo; Pimenta, Luiz André Freire; Rodrigues Jr., Antonio Luiz (My University, 2001)
Purpose: To investigate the microleakage of four hydrophilic adhesive systems: one multiple-bottles (Scotchbond Multi-Purpose Plus); two one-bottle (Single Bond, Stae); and one self-etching (Etch & Prime 3.0). Materials and Methods: 120 bovine incisor teeth were divided into four groups (n = 30) and Class V cavities were prepared at the cemento-enamel junction. The cavities were restored with the adhesive systems and with Z100 composite. The teeth were thermocycled 1,000 times between 5 ± 2°C and 55 ± 2°C with a dwell time of 1 min, and then placed in a 2% methylene blue dye (pH 7.0) for 4 hrs, washed and sectioned vertically through the center of the restorations. The qualitative evaluation was made by three examiners who distributed pre-established scores (0-4) for each tooth using a stereomicroscope at x30 magnification. Results: In enamel margins little microleakage was observed and the Kruskal-Wallis analysis did not show differences. In dentin margins the Kruskal-Wallis and multiple comparison analyses were applied: microleakage was significantly greater with Stae (median 3) and Scotchbond MP Plus (median 4). Single Bond (median 1) and Etch & Prime 3.0 (median 2) showed the best results in dentin margins, and the statistical analysis did not demonstrate differences in microleakage among these groups.